Extended hatching periods in the subantarctic lithodid crabs Lithodes santolla and Paralomis granulosa (Crustacea: Decapoda: Lithodidae) - Thatje, S. (2003)
Temporal pattern of hatching was studied in the subantarctic lithodid crabs Lithodes santolla (Molina) and Paralomis granulosa (Jaquinot) from the Argentine Beagle Channel. In both species, larval hatching occurred in low daily numbers over an extended period of up to several weeks, depending on hatch size. Low daily hatching activity and low oxygen-consumption rates in freshly hatched P. granulosa larvae are discussed as life history adaptations to, and/or physiological constraints by, the environmental conditions of high latitudes.